2009
DOI: 10.1097/aln.0b013e3181bbcc26
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Dexmedetomidine Added to Ropivacaine Causes a Dose-dependent Increase in the Duration of Thermal Antinociception in Sciatic Nerve Block in Rat

Abstract: Background The present study was designed to test the hypothesis that dexmedetomidine added to ropivacaine would increase the duration of antinociception to a thermal stimulus in a dose-dependent fashion in a rat model of sciatic nerve blockade. Methods Fifty adult Sprague Dawley rats (10 rats/group) received unilateral sciatic nerve blocks with 0.2 ml of 0.5% ropivacaine or 0.2 ml of 0.5% ropivacaine plus dexmedetomidine (2.7 μM [0.5 μg/kg], 11.7 μM [2 μg/kg], 34.1 μM [6 μg/kg], or 120.6 μM [20 μg/kg]) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
143
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 44 publications
4
143
2
3
Order By: Relevance
“…Brummett et al (21) have reported that 0.005% dexmedetomidine with the addition of 0.5% bupivacaine increases sensory and motor block times. Another study reported that ropivacaine added to dexmedetomidine is more likely to cause a sensory block than a motor block (22). Dexmedetomidine increased both the sensory and the motor block in our study, but the increase in the sensory block was greater.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Brummett et al (21) have reported that 0.005% dexmedetomidine with the addition of 0.5% bupivacaine increases sensory and motor block times. Another study reported that ropivacaine added to dexmedetomidine is more likely to cause a sensory block than a motor block (22). Dexmedetomidine increased both the sensory and the motor block in our study, but the increase in the sensory block was greater.…”
Section: Discussioncontrasting
confidence: 52%
“…Dexmedetomidine can be a useful adjuvant to add to local anesthetics during the postoperative period to provide analgesia without affecting mobilization. The perineural administration of dexmedetomidine in humans has not been approved by the Food and Drug Administration (22). On the other hand, there have been no reports of neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that dexmedetomidine exerts its effects through α 2 -adrenoceptor agonism. Brummett and colleagues' study investigating addition of dexmedetomidine to ropivacaine induced peripheral nerve block 19 . They administered dexmedetomidine in doses up to 20 μg.kg -1 , and the pH value of mixture of ropivacaine and dexmedetomidine was reported to be 5.69 ± 0.05, which is far more acidic than the pH values of drug mixtures measured in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It's α 2 -agonists reducing the release of norepinephine. It stimulates central presynaptic α2 receptor resulting in decreased noradrenaline release which in turn causes hypotension and bradycardia [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%